(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The National Education Policy (NEP) 2020 represents a transformative framework aimed at restructuring the Indian education system to meet the demands of the 21st century. One of its central objectives is to promote holistic development by integrating leadership and personality development into the educational process. This paper critically analyzes the provisions of NEP 2020 concerning educational leadership and personality development using secondary data sources, including policy documents, government reports, and existing scholarly literature. The study explores how the policy redefines the roles of teachers, institutions, and learners in fostering cognitive, emotional, social, and ethical growth. It further examines the relationship between leadership practices and personality development outcomes within educational settings. The findings suggest that while NEP 2020 provides a comprehensive and progressive vision, challenges related to implementation, teacher preparedness, infrastructure, and institutional leadership continue to hinder its effective execution. The paper concludes with recommendations aimed at strengthening leadership capacity, enhancing teacher training, and bridging the gap between policy and practice.